Post-embryonic development in Brazilian Social Wasps - Giannotti, Edilberto [UNESP]; da Rocha, Agda Alves (Springer Nature, 2020)
This chapter presents a review of morphological studies of the immature stages of social Brazilian wasps, discussing aspects such as oviposition; instar larva, pre-pupa, and pupal stages; as well as duration times of the immature stages. Those themes have been explored in less than 20% of the species recorded for that country. Most of those articles represent only descriptions of the last instar larva, so that there is still much to explore in terms of comparative studies.
Keywords: Instar; Larvae; Morphology; Polistinae; Pupae